The heating rate matters! contact heat evoked potentials in musicians and non-musicians - Fabian Sternkopf; Paulina S. Scheuren; Paulina S. Scheuren; Catherine R. Jutzeler; Catherine R. Jutzeler; André Lee; André Lee (Frontiers in Pain Research)
Classical musical training requires extreme levels of fine motor control, resulting in adaptive neuroplastic alterations in professional musicians. Additionally, musicians have a high prevalence of pain syndromes, which makes them an interesting group to research the influence of neuroplasticity on nociception. This report consists of two parts. Firstly, we present the results of a preliminary study comparing musicians and non-musicians with respect to their cortical responses to noxious heat stimuli at their hands and feet, using contact heat evoked potentials (CHEPs). Secondly, we quantitatively discuss the influence of the heating rates of two different stimulation devices on CHEPs when applying the exact same settings. For this, we measured the temperature curves of the devices’ stimuli and connected their respective heating rates to the resulting CHEPs. Musicians showed a significantly larger N2 latency difference between hands and feet (20.86 ms, p=0.0045), compared to non-musicians. Additionally, we found that, despite the exact same settings, different stimulation devices produced considerably different temperature curves. The resulting time difference between the stimulation devices of 104.78 ms explains the latency difference of the CHEPs produced by the respective device of 104.09 ms extremely well. This study underlines that musicians are an interesting model for neuroplasticity regarding nociception, as they respond differently to nociceptive stimuli. Moreover, it contributes to the understanding of the connection between a stimulation device’s heating rate and the resulting CHEPs, an important finding that has never been quantified before but has considerable consequences on the comparability of results.